The hyperphosphorylation of tau and Alzheimer's disease - Goedert, Michel (Henry Stewart Talks, 2010)
Alzheimer's disease, Extracellular plaques, Intracellular tangles, Tau filaments, Tau hyperphosphorylation, Other tauopathies, Mouse models of tauopathy, Protein kinase inhibitors, Protein phosphatase activators